MANAGEMENT OF DIABETES AND HYPERTENSION PATIENTS DURING HAJJ PILGRIMAGE - Roland Helmizar; Abdullah, Dessy; Prima Adelin; Lidia Dewi; Boy Hutaperi; Elfi Yulfienti; Chandra Adilla (Yayasan Nusantara Hasana Berdikari, 2024)
The Hajj, the annual Islamic pilgrimage to Mecca, is a significant event that poses unique challenges for individuals with chronic medical conditions, such as diabetes and hypertension. Diabetes, in particular, has been identified as a leading cause of morbidity and mortality during the Hajj. Patients with diabetes face a variety of logistical and environmental hurdles that can complicate their disease management, including exposure to extreme heat, lengthy periods of physical exertion, and difficulties in accessing and storing their medications. Approximately 20% of pilgrims with underlying illnesses who visit Mecca are diabetic, and these individuals are at an increased risk of developing serious complications, such as diabetic ketoacidosis, non ketotic hyperosmolar state, and hypoglycemia-induced fatigue or unconsciousness. Method: Implementation of community service activities. The planning stage begins with identifying problems and coordinating with related parties, there is a problem identification stage, an analysis is carried out related to diabetes and hypertension, and provides education related to hypertension and diabetes, and discussions with pilgrims. the results of the pilgrims' meeting understand well so that it can be concluded from this activity that pilgrims suffering from diabetes and hypertension can independently manage their treatment regimen and life style during the pilgrimage